1993
DOI: 10.1002/ajmg.1320460107
|View full text |Cite
|
Sign up to set email alerts
|

Angelman and Prader‐Willi syndrome: A magnetic resonance imaging study of differences in cerebral structure

Abstract: Recent improvements in magnetic resonance imaging techniques now allow the developing brain to be visualized in sufficient detail to perform "in vivo neuropathology." In this study we compared the cortical morphology in six children with Angelman and four with Prader-Willi syndrome. These two syndromes are of special interest because, although they are both caused by deletions in the same region of chromosome 15, Angelman children are far more severely affected, and do not speak. We measured the length of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…34 In light of the prevalence of speech and language disorders in individuals with PWS, 9,35 as well as an indication of decreased asymmetry reported earlier, 10 we expected to find decreased asymmetry again. In contrast, the larger group of PWS-D had a normal pattern of planum temporale asymmetry.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…34 In light of the prevalence of speech and language disorders in individuals with PWS, 9,35 as well as an indication of decreased asymmetry reported earlier, 10 we expected to find decreased asymmetry again. In contrast, the larger group of PWS-D had a normal pattern of planum temporale asymmetry.…”
Section: Discussionmentioning
confidence: 64%
“…One study, using magnetic resonance imaging (MRI), reported a lack of normal sylvian fissure asymmetry in four individuals with PWS. 10 A previous qualitative study from our group identified multiple brain abnormalities in individuals with PWS, including ventriculomegaly, sylvian fissure polymicrogyria, and incomplete sylvian fissure/ insula closure. 11 Although no abnormalities were seen in a comparison group of individuals with early-onset morbid obesity (EMO) of unknown etiology, we did note similarities between individuals with PWS and those with EMO on cognitive and achievement testing using the Woodcock-Johnson Tests of Cognitive Abilities and Achievement, Third Edition (WJ-III).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Such epigenetic events result in known aberrations of brain development. For example, Angelman syndrome-which presents with paroxysms of laughter, seizures, attention deficit, hyperactivity and aggressive behaviour-frequently shows anomalous cortical growth, resulting in cortical atrophy, microencephaly and ventricular dilation (Leonard et al 1993;Schumacher 2001;Williams et al 1989). …”
Section: Parent-of-origin Effectsmentioning
confidence: 99%